Safety review of tenofovir disoproxil fumarate/emtricitabine pre-exposure prophylaxis for pregnant women at risk of HIV infection. Issue 11 (2nd November 2021) - Stalter, Randy M.; Pintye, Jillian; Mugwanya, Kenneth K.
ABSTRACT: Introduction : Pregnancy is a period of elevated HIV risk in high-burden settings, motivating the need for prevention tools that are both safe for use and effective during pregnancy. Oral pre-exposure prophylaxis (PrEP) containing tenofovir disoproxil fumarate (TDF) is recommended by the World Health Organization, including for pregnant and postpartum women at substantial risk of HIV infection. Although TDF use during pregnancy appears generally safe, data on PrEP use during pregnancy remain limited. Areas covered : We provide an overview of the clinical pharmacology and efficacy of daily TDF-based PrEP and summarize current evidence on the safety of PrEP use by pregnant HIV-uninfected women. We synthesize relevant studies assessing pregnancy outcomes among pregnant women who are living with HIV (WLHIV) and using TDF-based therapy. Finally, we make comparison to the safety profiles of other emerging HIV prevention options. Expert opinion : The current evidence indicates that TDF/FTC PrEP use is not associated with increased risk of adverse pregnancy and early infant growth outcomes. While safety data are generally reassuring, there is need for continued accrual of data on growth and pregnancy outcomes in PrEP research, implementation projects, and controlled pharmacokinetic studies to support current evidence and to understand concentration–efficacy relationship in pregnant women.